2021
DOI: 10.1111/bdi.13045
|View full text |Cite
|
Sign up to set email alerts
|

Neural changes in youth at high risk for bipolar disorder undergoing family‐focused therapy or psychoeducation

Abstract: Background: Patients with mood disorders may benefit from psychosocial interventions through changes in brain networks underlying emotion processing. In this study, we used functional magnetic resonance imaging (fMRI) to investigate treatment-related changes in emotion processing networks in youth at familial high risk for bipolar disorder (BD).Methods: Youth, ages 9-17, were randomly assigned to family-focused therapy for high-risk youth (FFT-HR) or an active comparison treatment, Enhanced Care (EC).Before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These two imaging conditions result in different research results and most studies utilised task state. In the task-based studies in BD, researchers found brain activation changes, after treatment in the dorsolateral prefrontal cortex (DLPFC), cingulate gyrus (CG), insula and temporal lobe (Garrett et al, 2021; Haldane et al, 2008; Jogia, Haldane, Cobb, Kumari, & Frangou, 2008). Moreover, due to the diversity of neuropsychological tasks as well as task-based activation of specific brain regions, the consistence and applicability were lacking in the task-based state studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two imaging conditions result in different research results and most studies utilised task state. In the task-based studies in BD, researchers found brain activation changes, after treatment in the dorsolateral prefrontal cortex (DLPFC), cingulate gyrus (CG), insula and temporal lobe (Garrett et al, 2021; Haldane et al, 2008; Jogia, Haldane, Cobb, Kumari, & Frangou, 2008). Moreover, due to the diversity of neuropsychological tasks as well as task-based activation of specific brain regions, the consistence and applicability were lacking in the task-based state studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this study, we also divided the tasks into these two categories. During emotional tasks, the brain activity in the inferior frontal gyrus (IFG), anterior cingulate cortex (ACC) and amygdala changed (Favre et al, 2013; Garrett et al, 2021), while studies found that the brain activation in hippocampus, superior frontal gyrus (SFG) and CG changed during cognitive tasks (Deckersbach et al, 2018; Haldane et al, 2008). We aimed to identify brain activation changes in task-specific activation for emotional tasks v. cognitive tasks at pre and post treatment, whilst combining both aforementioned treatments (psychotherapy and drug therapy).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, classification models based on hippocampal connectivity patterns showed high discriminative utility to identify those individuals who are highly vulnerable to the onset of mood disorders; hippocampal connectivity has even been used as a marker for early detection of mood disorders (Zou et al., 2022). Conversely, response to antidepressant treatment, cognitive behavioral therapy, and physical activity may be linked to the improvement in symptoms of emotional dysregulation, possibly through their effects on the hippocampus that lead to its altered cellular structure (Garrett et al., 2021; Gorham, Jernigan, Hudziak, & Barch, 2019; Whittle, 2019). However, the directions of the topographic changes of youth at high risk (higher in high‐risk youth) in the above brain regions might differ from those of individuals with mood disorders (Roberts, Wen, et al., 2022; Zou et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They found that FFT can help syndrome improvement by activating the dorsolateral prefrontal cortex in visual attention networks, which is helpful for completing tasks. Moreover, the improved interaction inside the family can help develop the prefrontal cortex, preventing youths at risk of BD from developing further mood symptoms [37]. Moreover, a bottom-up processing change in neural response was found in the FFT, which is quite different from the neural response with EC [38].…”
Section: The Development (2016-2021)mentioning
confidence: 96%